PENGARUH GAYA KEPEMIMPINAN DAN ESPRIT DECORPS TERHADAP KINERJA KARYAWAN DI PT YUSIKA SUKSES MANDIRI DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Dinni Suci; Ervita Safitri; Henny Pramasary (Ikatan Dosen Menulis, 2025)
This study aims to identify and prove as well as analyze the direct effect of leadership and Esprit de Corps on job satisfaction, the influence of leadership and Esprit de Corps on performance, the influence of motivation on performance and the influence of leadership and Esprit de Corps on employee performance meditated by motivation with samples in this research are employees of PT. Yusika Sukses Mandiri totaling 82 people. Analysis of research data using descriptive and inferential statistical methods. Analysis of the model using the Structural Equation Model (SEM) with the composition of Substructure: Leadership and Esprit de Corps as exogenous variables, Performance as endogenous variables, and motivation as intervening variables. From the results of hypothesis testing it was found as follows: 1) Leadership has an effect on motivation 2) Esprit de Corps has an effect on motivation 3) Leadership has an effect on Performance 4) Esprit de Corps has an effect on Performance 5) Motivation has an effect on Performance.